Notes on the genus Dendrocerus Ratzeburg (Hymenoptera, Megaspilidae) from China, with description of two new species - Wang, Xu; Chen, Huayan; Mikó, István; Huang, Yixin; Zhu, Chaodong (Journal of Hymenoptera research, 2021)
Species of the genus Dendrocerus Ratzeburg, 1852 (Hymenoptera: Megaspilidae) from China were studied. Six species are recorded, of which two known species, D. carpenteri (Curtis, 1829) and D. laticeps (Hedicke, 1929) are re-described; and two species are described as new to science, D. anisodontus Wang, Chen and Mikó sp. nov. and D. bellus Wang, Chen and Mikó sp. nov. . Sequences of the 28S rDNA were generated to associate both sexes of the same species.